Cryo-electron tomography and 3-D analysis of the intact flagellum in Trypanosoma brucei - Höög, J; Bouchet-Marquis, C; McIntosh, JR; Hoenger, A; Gull, K (Elsevier, 2012)
Trypanosoma brucei is a uni-cellular protist that causes African sleeping sickness. These parasites have a flagellum that is attached to the cell body and is indispensible for its motility. The flagellum consists of a canonical 9+2 axoneme and a paraflagellar rod (PFR), an intricate tripartite, fibrous structure that is connected to the axoneme. In this paper we describe results from cryo-electron tomography of unperturbed flagella. This method revealed novel structures that are likely involved in attaching the flagellum to the cell. We also show the first cryo-electron tomographic images of a basal body in situ, revealing electron dense structures inside its triplet microtubules. Sub-tomogram averaging of the PFR revealed that its distal region is organized as an orthorhombic crystal.